(untitled) (Research, Society and Development, 2021)
The sunflower is a versatile plant that has attractive inflorescences marketed as a cut flower or vase. The objectives of the work were to evaluate the cultivation of ornamental sunflower in different substrates and pot sizes, and to verify if this cultivation corresponds to the commercialization pattern established by Veiling Holambra. The experimental design used was completely randomized, in a 2x2 factorial scheme (two substrates (commercial and teak residue) and two vessel sizes (n° 10 and 14), with 20 replicates, totaling 80 vessels. The diameter of the stem, the internal and external chapter were evaluated; plant height; number of leaves per plant and buds, and period of durability of the inflorescence. It was concluded that the combination of commercial substrate and pot nº 14 was efficient in the production of ornamental sunflower. In both tested substrates, the plants fit the commercialization pattern established for the species.